Availability of services in registered retirement villages in Queensland, Australia: a content analysis - Hu, Xin; Xia, B.; Buys, L.; Skitmore, M. (Wiley-Blackwell Publishing Asia, 2017)
Objective: The study investigates and compares the services available in different types of registered retirement villages in Queensland (QLD). Methods: A content analysis based on official websites of 175 registered villages in QLD, Australia, is presented. Results: This study identifies 82 services, with activity organisation, emergency response, hairdressing and transportation being most frequently available to residents. The number of services available is associated with the village size and financial type, with residents living in large private villages having access to significantly more services. Conclusion: The research findings reveal the state of the art of current industry practice. They provide useful implications for stakeholders. For instance, residents who prefer to get access to various services should focus more on large private villages. Developers can check their service delivery environment to confirm its balance with residents’ competencies. The government can propose innovative initiatives to promote the delivery of appropriate services in villages.